TINJAUAN HUKUM ATAS CLICK WRAP AGREEMENT PADA KONTRAK BAKU ELEKTRONIK TERKAIT TRANSAKSI ELEKTRONIK - santoso, edy (JURNAL ILMIAH LIVING LAW, 2015)
Nowadays, the development of technology information has tremendous impact on aspects of cultural, economic, social and legal. In the area of business transactions, for example, a signature is a common form of agreement in the purchase agreement. Today, it has been changed; the form agreement was made so simple by âclickâ only through using "click warap agreement" to indicate approval of the contents of the standard online agreement. It is recognized as a form of discovery of a finding law in the area of purchase agreement, which needs to be studied whether against the law in Indonesia or not. Therefore, this paper examines the legal review of click wrap agreement on the online agreement in e-commerce transactions under Indonesia law